Risk Factors of Computer Vision Syndrome: A Review of Ocular Causes Among School and College Students - Viddina Xyquizintya Maroef; Retno Adriyani; I Wayan Gede Artawan Eka Putra (Universitas Airlangga, 2023)
Introduction: According to the results of a survey published in 2022, mobile phone users have reached two-thirds (67.1%) of the world population. This number has increased by 1.8% over the past year, which is equivalent to 95 million new mobile users. However, gadgets are often misused and can cause a health problem called Computer Vision Syndrome (CVS). This study aimed to identify risk factors for the occurrence of ocular CVS symptoms among school and college students. Discussion: This study was conducted using the literature review method. The main sources for this study were articles obtained through the selection process by setting inclusion and exclusion criteria. This study showed that from a total of 1,763 articles found, 27 articles met the predetermined criteria. A total of 18 of the 27 articles (66.7%) had college student as respondents, and 24 of the 27 articles used cross-sectional research methods (88.9%). In this study, 16 CVS ocular symptoms were found. The risk factors for CVS were individual characteristics (students aged under 18 years and students aged 18–25 years, and gadget users with contact lenses or glasses), smartphone users, individual habits, and ambient lighting while operating gadgets. Conclusions: This study concludes that students are at risk of experiencing CVS if they do not support gadget use with habits such as implementing rest periods between activities using gadgets.